Management of Girl Competencies in Improving the Quality of Education Graduates - Rahayu Detik Susilawati; Ulfiah Ulfiah; Nanang Hanafiah; Achmad Mudrikah (International Journal of Nusantara Islam, 2019)
Innovation is a change or an idea that is deliberately created based on changes that are original in nature, modification or collaboration can have physical or behavioral rewards. Innovation in the field of education is not something new to do, in fact, almost every time new things are found to be a method or method used to achieve the vision and mission of education, of course good management is needed to regulate how the use of existing competencies becomes a source of educational strength in education. quality improvement process. In general, the Management of Teaching and Learning Competencies in Improving the Quality of Education Graduates, is oriented towards the vision, mission, and goals that must be realized at a certain time through an analysis of the resources owned by the school, both human resources and other resources, so that the achievement of school goals can be realized. In reality, the Management of Teaching and Learning Competencies in Improving the Quality of Education Graduates is still not effective because it still faces various obstacles, especially human resources and school resources.